Combates sanitários e embates científicos: Emílio Ribas e a febre amarela em São Paulo Sanitary battles and scientific clashes: Emílio Ribas and yellow fever in São Paulo - Marta de Almeida (História, Ciências, Saúde: Manguinhos)
Este artigo analisa o combate à febre amarela, capitaneado por Emílio Ribas, dirigente do Serviço Sanitário de São Paulo no período de 1898 a 1917. Determinado a controlar a epidemia em todos os seus aspectos, Ribas aderiu convictamente, desde o início, à concepção microbiológica. A análise das experiências relacionadas à febre amarela, feitas no Hospital de Isolamento de São Paulo, em 1902-03, sob a direção de Emílio Ribas, revela a existência de um ambiente instável e tenso envolvendo os cientistas e profissionais vinculados ao Serviço Sanitário de São Paulo. O artigo destaca a importância das experiências para a afirmação das novas concepções e práticas médico-sanitárias. A análise dos trabalhos publicados sobre a febre amarela permite apreender aspectos da transformação dos significados do mal amarílico, bem como suas implicações para a história da saúde pública em São Paulo. Emílio Ribas, an administrative physician and sanitarian from São Paulo, was an advocate of the microbiological conception during the long period when he directed the Serviço Sanitário de São Paulo (1898-1917). This article offers a brief analysis of his stance in the fight against yellow fever during the early 20th century, considered a highlight of his career. The scientists and professionals linked to this sanitary agency in São Paulo found themselves in a tense, unstable work environment, where experimental proof played an important role in corroborating new medical-sanitary conceptions and practices. The article takes a close look at the medical experiments on yellow fever directed by Emílio Ribas and conducted at São Paulo’s Hospital de Isolamento in 1902-03. It examines these same studies in an effort to better understand how the significance of yellor fever was transformed and to explore its implications regarding the history of public health in São Paulo.